Source–sink recruitment of red snapper: Connectivity between the Gulf of Mexico and Atlantic Ocean. (24th August 2022) - Karnauskas, Mandy; Shertzer, Kyle W.; Paris, Claire B.; Farmer, Nicholas A.; Switzer, Theodore S.; Lowerre‐Barbieri, Susan K.; Kellison, G. Todd; He, Ruoying; Vaz, Ana C.
Abstract: Geopolitical fishery management boundaries are often misaligned with the ecological population structure of marine species, which presents challenges for assessment and management of these species. Red snapper, Lutjanus campechanus, is an iconic and heavily exploited species in both the US Gulf of Mexico and off the southeastern US Atlantic coast and is managed separately in the two jurisdictions. It is hypothesized that the Atlantic red snapper stock is sustained partially by larval subsidies from the Gulf of Mexico. Here we use a biophysical modeling approach to simulate recruitment of red snapper across the entire Southeastern US region, and quantify rates of larval exchange across management jurisdictions. The biophysical framework simulates realistic red snapper behaviors and traits with respect to spatial distribution and timing of spawning, larval vertical migration and pelagic larval duration, and settlement habitat. Our results suggest that areas of the West Florida Shelf south of Tampa Bay are important sources of larvae for the Atlantic population, supplying as much as one third of the recruitment during some years. Yet, contributions of Gulf‐spawned red snapper to the Atlantic stock are highly dynamic given large variability in spatial and temporal patterns of red snapper recovery in each region. As such, effective management of the Gulf of Mexico red snapper stock, particularly the spawning population in southwest Florida, may have important consequences for the sustainable harvest of red snapper off the Atlantic coast.